Basic Fibroblast Growth Factor Attenuates Injury in Myocardial Infarction by Enhancing Hypoxia-Inducible Factor-1 Alpha Accumulation - Rao, Zhiheng; Shen, Danping; Chen, Jiahui; Jin, Lushen; Wu, Xueping; Chen, Ming; Li, Lei; Chu, Maoping; Lin, Jiafeng (Frontiers in Pharmacology, 2020)
The combination of antiapoptotic and angiogenic actions may represent a pharmacotherapeutic strategy for the treatment of myocardial infarction. Fibroblast growth factor (FGF) is expressed in various cell types and is involved in their survival, migration, and proliferation. Myocardial microvascular endothelial cells were divided into four groups, the sham, hypoxia, basic FGF (bFGF), and bFGF plus 2-methoxyestradiol groups, and subjected to in vitro apoptotic analysis and Matrigel assays. An in vivo model of myocardial infarction was established by ligaturing the left coronary artery of mice in the four treatment groups. Cardiac performance, myocardial injury, endothelial cell angiogenesis, and myocardial apoptosis were assessed. bFGF administration after myocardial infarction improved cardiac function and cell viability, attenuated myocardial injury and apoptosis, and enhanced angiogenesis. Western blotting of AKT, p-AKT, HIF-1α, VEGF, p53, BAX, and Bcl-2 showed that bFGF increased HIF-1α, p-AKT, VEGF, and Bcl-2 and decreased BAX protein levels. The results of the present study indicated that bFGF attenuates myocardial injury by inhibiting apoptosis and promoting angiogenesis. These findings suggest a novel molecular mechanism by which bFGF protects against myocardial infarction.